PENINGKATAN LITERASI SAINS MELALUI MODEL PROBLEM BASED LEARNING DI SMA INTEGRAL AR-ROHMAH MALANG - Abu Rizal Afiat (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2022)
Scientific literacy skills are needed in facing the 21st century. However, the scientific literacy level of students in Indonesia is still below the international average score. This is also in line with the conditions that occur in class XI students of SMA Integral Ar-Rohmah, students are not used to solving contextual problems and students' scientific literacy is also still low. One learning model that can facilitate students' scientific literacy skills is Problem Based Learning. This research is a classroom action research, with a cycle model research design consisting of planning, action implementation, evaluation and reflection. The results showed that students experienced an increase in scientific literacy between pre-cycle and cycle one. This can also be proven from the posttest average score which is higher than the pretest, with an average posttest score of 75.17 and an average pretest score of 49.65. There were 22 or 75.86% of students who had a scientific literacy score of more than 70 after being treated with problem-based learning models. Thus, the indicators of the success of this research have been achieved, because more than 70% of students achieved a minimum completeness score after learning using the problem based learning model. Abstrak Kemampuan literasi sains sangat diperlukan dalam menghadapi abad 21. Namun, tingkat literasi sains peserta didik di Indonesia masih di bawah rata-rata skor internasional. Hal ini juga sejalan dengan kondisi yang terjadi pada peserta didik kelas XI SMA Integral Ar-Rohmah dimana peserta didik belum terbiasa memecahkan permasalahan kontekstual dan literasi sains peserta didik juga masih rendah. Salah satu model pembelajaran yang dapat memfasilitasi kemampuan literasi sains siswa adalah Problem Based Learning. Penelitian ini merupakan penelitian tindakan kelas, dengan desain penelitian model siklus yang terdiri dari perencanaan, pelaksanaan tindakan, evaluasi dan refleksi. Hasil penelitian menunjukkan bahwa peserta didik mengalami peningkatan literasi sains antara pra-siklus dan siklus satu. Hal ini juga dapat dibuktikan dari skor rata-rata posttest yang lebih tinggi daripada pretest, dengan rata-rata skor posttest sebesar 75,17 dan rata-rata skor pretest sebesar 49,65. Terdapat 22 atau 75,86% peserta didik memiliki skor literasi sains lebih dari 70 setelah diberikan perlakuan model pembelajaran problem based learning. Dengan demikian, indikator keberhasilan penelitian ini telah tercapai, karena lebih dari 70% peserta didik mencapai nilai ketuntasan minimal setelah belajar dengan menggunakan model problem based learning.